Comparative study on urban growth process in developing countries: case study Phnom Penh and Kuala Lumpur - Hj. Mohd. Noor, Norzailawati; Faizah, Ahmad; Muhammad, Ibrahim; Nuraulia, Rusni (2013)
The purpose of this paper is to study the nature of on-going transition in developing countries, the quality and uncertainty of existing urbanisation forecast. This paper provides a broad overview on the existing urban growth process and discussing the available evidence on patterns and trends of growth respectively. Two capital cities namely Phnom Penh in Royal Government of Cambodia and Kuala Lumpur in Malaysia were used in assessing the process of urban growth of developing countries. Two different pattern of urban growth process were compared and analysed to establish a real development scenario. Phnom Penh and Kuala Lumpur development assess the challenges associated with urban growth that lie ahead and identify the key area of policy that been required. It ends by highlighting the growing needs for vibrant urban research agenda to adequate future policy.